Pengaruh Pendidikan Pencegahan Stunting Terhadap Pengetahuan Kader Posyandu - Dian Septyana Tri Astuti (Jurnal Ilmiah Kesehatan, 2022)
Stunting is a chronic nutritional problem characterized by a short body (stunted). Health education is held as a learning effort to improve the Posyandu cadres’ knowledge of stunting prevention. The Posyandu cadres’ role is vital to the early prevention of stunting. This study aimed to figure out the influence of health education on Posyandu cadres’ knowledge of stunting prevention in Keniten urban village, Ponorogo. This study used pre-experimental designs, namely a one-group pretest-posttest design. The sampling technique used in this study was total sampling with 35 samples in total. The data collection method was questionnaires. The statistical test was done using the Wilcoxon test. The result showed a significant improvement in the cadres’ knowledge level before and after giving health education with an average score of 81 increased to 90. The statistical test result showed a p-value of 0.005 (≤0.05), indicating a significant effect of health education on Posyandu cadres’ knowledge level of stunting prevention in Keniten urban village. The improvement on posyandu cadres’ knowledge of stunting prevention level happens due to health education. Providing information on stunting prevention or conducting training regularly by the Community Health Center to the Posyandu cadres to improve their knowledge to be better.